2011
DOI: 10.1007/s10637-011-9682-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of the poly(ADP-ribose) polymerase (PARP) inhibitor, olaparib (AZD2281) in combination with topotecan for the treatment of patients with advanced solid tumors: a phase I study

Abstract: Further development of olaparib and topotecan in combination was not explored due to dose-limiting hematological AEs and the resulting sub-therapeutic MTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 24 publications
(32 reference statements)
0
84
1
1
Order By: Relevance
“…However, a number of early phase clinical trials have reported severe bone marrow toxicity with such therapeutic combinations [5][6][7][8][9][10] which could in part be attributed to suboptimal dosing schedules. 8 Non-invasive in vivo imaging of PARP-1 using a radiolabeled PARPi and techniques such as Positron Emission Tomography (PET) or Single-Photon Emission Tomography (SPECT) could be used to assess the duration of PARP-1 inhibition in different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of early phase clinical trials have reported severe bone marrow toxicity with such therapeutic combinations [5][6][7][8][9][10] which could in part be attributed to suboptimal dosing schedules. 8 Non-invasive in vivo imaging of PARP-1 using a radiolabeled PARPi and techniques such as Positron Emission Tomography (PET) or Single-Photon Emission Tomography (SPECT) could be used to assess the duration of PARP-1 inhibition in different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the 2274 patients, several types of cancers were reported, such as ovarian, lung, breast, and gastric cancers. Besides these, many trials [26][27][28][29][30][31][32] in different kinds of cancers not eligible for inclusion are still under way. Although the results have not come out, it is possible that PARP inhibitors may work in patients against some certain types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have led to clinical trials of PARP inhibitors in combination with chemotherapeutics that lead to DNA damage (Table 1), with the PARP inhibitor blocking the subsequent DNA repair mechanisms selectively in cancer cells. Some of the drugs being used with PARP inhibitors include platinum based DNA damaging agents such as cisplatin, carboplatin, oxaliplatin; alkylating agents like Temozolomide (TMZ) and topoisomerase inhibitors such as Camptothecin (CPT) and its derivatives (irinotecan and topotecan) [19][20][21][22][23][24][25]. TMZ therapy, when combined with radiation induces single stranded breaks (SSBs) and hence is the direct target of PARP inhibitors.…”
Section: Combination Therapy With Chemotherapeutics and Radiationmentioning
confidence: 99%